Juridical Analysis of Sexual Harassment Committed by Individual TNI Members - Maulana, Rizal Fa’jrin; Prasetyo, Teguh; Jaeni, Ahmad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Indonesia is a legal state based on Pancasila and the 1945 Constitution of the Republic of Indonesia (UUDNRI 1945). The concept of a legal state proposed by Wiryono Projodikoro defines it as a state where rulers or the government, as the state organizers, are bound by the applicable legal regulations in carrying out state duties. The Indonesian National Armed Forces (TNI) is an integral part of the legal community, playing a crucial role in supporting the formation of legal culture within its ranks. Legal awareness within the TNI is upheld when military personnel, as supporters of legal culture, actively contribute by adhering to all applicable regulations and making the law a guide in their behavior and actions. Despite having rules in place governing prohibited behaviors for military personnel, the reality indicates that there are still individuals within the TNI involved in criminal activities. When a military member engages in sexual harassment, it creates dissonance in the execution of military duties and can undermine public trust in the military institution, which should be responsible for safeguarding and protecting the community. Unfortunately, reality does not always align with expectations, as evident in cases involving TNI members, who are a vital force in maintaining the integrity of the Republic of Indonesia. This phenomenon not only highlights individual problems but also significantly impacts public trust in the structure of the national defense institution. Therefore, when a TNI member or soldier is involved in sexual harassment, the most severe punishment that can be imposed is dismissal, or in other words, removal from their position. This sanction is not only administrative but also includes criminal consequences regulated in the Criminal Code. Protection of the integrity of the TNI, therefore, involves not only internal disciplinary aspects but also engages in a legal process that can provide criminal sanctions commensurate with the crime of sexual harassment committed by military personnel. Military members, being part of a unit, form an integrated family. It seems as though within a military unit, an "autonomous power" is created specifically within that unit. This military unit has a commander and a deputy commander, supported by section officers and unit commanders. When issues arise within the military unit, efforts for resolution are made, as much as possible, by the appointed unit commander.